Membangun Kerukunan dalam Bingkai Pluralisme Agama: Analisis Gagasan Pemikir Muslim Kontemporer: Fostering Interfaith Harmony within the Context of Religious Pluralism: Insights from Contemporary Muslim Scholars - Armayanto, Harda (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
This article aims to analyze the concept of interfaith harmony through the approach of religious pluralism proposed by contemporary Muslim thinkers. It explores ideas and efforts to foster harmony amidst the intolerance often found among diverse ethnic and religious groups. The arguments of pluralists merit examination and analysis, considering the approach of religious pluralism they adopt has evoked both support and controversy in society. Moreover, disputes over the meanings and concepts of this approach even among its proponents are noteworthy. This qualitative research is based on library research, utilizing both print and digital sources. Initially, the article outlines the pluralists' arguments for building harmony through religious pluralism, which are then subjected to critical analysis. It finds that the concept of religious pluralism embodies elements of truth relativism and the desacralization of religious values. Consequently, efforts to foster harmony proposed by pluralists often conflict with religious values, especially Islamic teachings, such as denying claims of salvation, endorsing same-sex marriage, interfaith marriage, and permitting apostasy, viewed as forms of religious freedom claimed to align with the commandments of Allah. Abstrak Artikel ini bertujuan untuk menganalisis konsep kerukunan antar umat dengan pendekatan pluralisme agama yang digagas oleh para pemikir Muslim kontemporer. Gagasan dan upaya membangun kerukunan berkait dengan perilaku intoleransi yang jamak terjadi di tengah keragaman suku dan agama. Argumen para pluralis layak dikaji dan dianalisis mengingat pendekatan pluralisme agama yang mereka gunakan menuai pro dan kontra di masyarakat. Bahkan, perebutan makna dan konsep tentang pendekatan ini terjadi di antara mereka sendiri. Penelitian dalam artikel ini bersifat kualitatif dengan berbasis pada data kepustakaan, baik cetak maupun digital. Mula-mula, peneliti memaparkan argumen para pluralis membangun kerukunan dengan pendekatan pluralisme agama untuk kemudian dianalisis secara kritis. Dalam tulisan ini ditemukan bahwa gagasan pluralisme agama mengandung relativisme kebenaran dan mendesakralisasi nilai-nilai agama. Oleh karenanya, upaya-upaya membangun kerukunan yang digagas para pluralis sering kali bertentangan nilai-nilai agama, utamanya dengan ajaran Islam, seperti penafian klaim keselamatan, pernikahan sesama jenis, pernikahan beda agama, hingga membolehkan murtad karena dianggap sebagai bentuk kebebasan beragama yang diklaim sejalan dengan perintah Allah.